2015
DOI: 10.1016/j.neubiorev.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Microstates in resting-state EEG: Current status and future directions

Abstract: Electroencephalography (EEG) is a powerful method of studying the electrophysiology of the brain with high temporal resolution. Several analytical approaches to extract information from the EEG signal have been proposed. One method, termed microstate analysis, considers the multichannel EEG recording as a series of quasi-stable “microstates” that are each characterized by a unique topography of electric potentials over the entire channel array. Because this technique simultaneously considers signals recorded f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
695
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 642 publications
(744 citation statements)
references
References 88 publications
(141 reference statements)
45
695
1
3
Order By: Relevance
“…Previous studies have consistently reported that EEG microstates range in duration from 60-120 ms (Koenig et al, 2002); for a review see (Khanna et al, 2015), in accordance with previous findings regarding the duration required for conscious experience. For example, sequentially presented stimuli are not perceived as separate when they follow each other within less than 80 ms (Efron, 1970).…”
Section: Microstates and The Phenomenon Of Discrete Epochs Of Cognitionsupporting
confidence: 86%
See 3 more Smart Citations
“…Previous studies have consistently reported that EEG microstates range in duration from 60-120 ms (Koenig et al, 2002); for a review see (Khanna et al, 2015), in accordance with previous findings regarding the duration required for conscious experience. For example, sequentially presented stimuli are not perceived as separate when they follow each other within less than 80 ms (Efron, 1970).…”
Section: Microstates and The Phenomenon Of Discrete Epochs Of Cognitionsupporting
confidence: 86%
“…Microstate map A exhibits a left-right orientation, map B exhibits a right-left orientation, map C exhibits an anterior-posterior orientation, and map D exhibits a fronto-central maximum. Even if more cluster maps are selected, these four maps seem to consistently dominate the data across different age ranges, conditions (e.g., sleep and hypnosis), and pathological states (Khanna et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the very high time resolution of the EEG, the microstate analysis allows the isolation of microstates with a typical duration of 60-120 milliseconds. Cluster analyses of the microstate topographies showed that in eyes closed resting EEG, four classes of microstate topographies explain a large amount (up to 90%) of the variance in the data (Khanna et al 2015;Koenig et al 2002;Wackermann et al 1993); they also replicate well over a large age range (from 6 to 80 years) and over different studies (see Koenig et al 2002). In addition to their duration, the EEG microstates are characterized by the parameters coverage and occurrence that describe the percentage of time spent and the number of occurrences per second respectively of microstates of a given class.…”
Section: Introductionmentioning
confidence: 99%